2011
DOI: 10.1186/1756-3305-4-102
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Entamoeba histolytica infection in an agricultural community in Hanam province, Vietnam

Abstract: BackgroundEntamoeba histolytica is an important protozoan intestinal infection in resource-poor settings, including Vietnam. The study objective was to assess risk factors of E. histolytica infection in a community in Vietnam, where wastewater and human excreta are used in agriculture. A case-control study was conducted among residents of Hanam province, Northern Vietnam. Cases (n = 46) infected with E. histolytica and non-infected controls (n = 138) were identified in a cross-sectional survey among 794 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 17 publications
5
53
1
1
Order By: Relevance
“…moshkovskii and this finding is consistent with a previous study from Brazil [37] and Iran [38]. By contrast, recent reports from Kenya, Yemen, Vietnam, and Tajikistan found no association between E. histolytica infection and the consumption of raw vegetables [27], [29], [39], [40]. We observed that tapioca shoots, wild fern shoots and locally planted leaves are the main raw vegetables as salad by the Senois; they usually do not wash these vegetables before eating.…”
Section: Discussionsupporting
confidence: 91%
“…moshkovskii and this finding is consistent with a previous study from Brazil [37] and Iran [38]. By contrast, recent reports from Kenya, Yemen, Vietnam, and Tajikistan found no association between E. histolytica infection and the consumption of raw vegetables [27], [29], [39], [40]. We observed that tapioca shoots, wild fern shoots and locally planted leaves are the main raw vegetables as salad by the Senois; they usually do not wash these vegetables before eating.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we showed that the prevalence of E. dispar, E. histolytica and C. spp is low for patients with GI symptoms and in a healthy group without GI symptoms. The prevalence of E. dispar in the adult population is similar to that described in other studies from Vietnam concerning E. histolytica (18,19). However, the prevalence of E. histolytica may be overestimated because typing was not made by PCR.…”
Section: Discussionsupporting
confidence: 88%
“…The interlinkages between different contamination sources and transmission routes are essential in these types of studies. Pham-Duc et al [75] found that hygiene was the main pre-disposing factor to an increased risk of parasitic infections (mainly protozoan) rather than exposure to wastewater or sludge. The epidemiological studies highlight a high incidence of STH infections among farmers and consumers of vegetables irrigated with wastewater or on sludge amended soil.…”
Section: Wastewatermentioning
confidence: 99%